Hubungan Kualitas Air Sumur Bor Dengan Kejadian Diare Kelurahan Bakung Kecamatan Biringkanaya Kota Makassar - Tatiek, Tatiek Sri Handayani; Andi Surahman Batara; Hidayat; Alfina Baharuddin; Septiyanti (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Clean water is a vital and basic need for all living things. One source of clean water is bore well water The quality of the borehole water used must meet the requirements in accordance with the standards set out in the Minister of Health Regulation No. 416 of 1990. In order to maintain the quality of the water, it is necessary to pay attention to the requirements for bore wells. The purpose of this study was to determine the relationship between bore well water quality and the incidence of diarrhea in the RT. 03 RW. 01 Bakung Village, Biringkanaya District, Makassar City. This research is an analytical survey research (observational analytic) with a cross sectional design. The method used is interviews, direct observation and examination of water samples in the Makassar City Health Office laboratory. These results were analyzed using univariate and bivariate analysis and then tested using statistical tests (chi square). The results showed that there was a relationship between well construction and the incidence of diarrhea (p = 0.004 < = 0.05), there was a relationship between the distance of the pollutant source and the incidence of diarrhea (p = 0.001 < = 0.05). There was no relationship between the microbiological content of drinking water and the incidence of diarrhea (p = 0.184 > = 0.05). It is recommended to owners of boreholes that do not meet the requirements for the physical condition of their wells to immediately repair the wells to produce good quality borehole water and meet the requirements